2021
DOI: 10.1038/s41598-021-82135-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on emotion recognition from dynamic multimodal expressions and vocalizations

Abstract: Age-related differences in emotion recognition have predominantly been investigated using static pictures of facial expressions, and positive emotions beyond happiness have rarely been included. The current study instead used dynamic facial and vocal stimuli, and included a wider than usual range of positive emotions. In Task 1, younger and older adults were tested for their abilities to recognize 12 emotions from brief video recordings presented in visual, auditory, and multimodal blocks. Task 2 assessed reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Although, it is worth noting that happiness is the only positive emotion included in these studies. Some healthy aging research has suggested that the positivity effect might be caused by ceiling effects (that happiness is a lot easier to distinguish from the negative emotions) [26]. Despite this, Johnson et al [27] reported impaired recognition of anger, disgust, fear, sadness, and surprise in a cross-sectional population of 475 pre-manifest HD patients.…”
Section: Emotional Recognitionmentioning
confidence: 99%
“…Although, it is worth noting that happiness is the only positive emotion included in these studies. Some healthy aging research has suggested that the positivity effect might be caused by ceiling effects (that happiness is a lot easier to distinguish from the negative emotions) [26]. Despite this, Johnson et al [27] reported impaired recognition of anger, disgust, fear, sadness, and surprise in a cross-sectional population of 475 pre-manifest HD patients.…”
Section: Emotional Recognitionmentioning
confidence: 99%
“…See electronic supplementary material, table S1 for internal validity of the emotion identification measures. The stimuli used in the present task were well-validated and used in other emotion-related research [87][88][89], including research with older adults to assess age-related differences in dynamic perceptual processing and emotion identification [90,91]. Stimuli were counterbalanced by age and sex of the actors, emotion type, and modality.…”
Section: (Iii) Dynamic Emotion Identification Taskmentioning
confidence: 99%
“…Participants were required to respond for the entire 60 seconds before they could move on to the next question. The free speech prompt was used to establish positive or negative valence (Cortes et al, 2021), which has been shown in multiple other studies to extract acoustic or linguistic information that may be relevant for conditions like depression and dementia (Sumali et al, 2020).…”
Section: Free Speechmentioning
confidence: 99%